2018
DOI: 10.3168/jds.2017-13973
|View full text |Cite
|
Sign up to set email alerts
|

Feeding increasing amounts of ruminally protected choline decreased fatty liver in nonlactating, pregnant Holstein cows in negative energy status

Abstract: The objectives were to determine the optimal feeding amount of choline in a ruminally protected form to reduce the triacylglycerol (TAG) concentration in liver and to increase TAG in blood plasma of dairy cows. Pregnant, nonlactating multiparous Holstein cows (n = 77) were blocked by body condition score (3.59 ± 0.33) and assigned to treatment at 64 ± 10 d before calculated calving date. Dietary treatments were top-dressing of 0, 30, 60, 90, or 120 g/d of ruminally protected choline (RPC; Balchem Corp., New Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 73 publications
7
65
2
4
Order By: Relevance
“…Choline has well-demonstrated lipotropic effects in laboratory animals (Cole et al, 2012) and dairy cows (Cooke et al, 2007;Elek et al, 2013;Zenobi et al, 2018b), and overconditioned prepartum dairy cows have an increased risk of fatty liver (Bobe et al, 2004). Therefore, it is reasonable to suggest that potential effects of choline on improving lipid intermediary metabolism and lactation performance might be more easily observed in cows at an increased risk for hepatic lipido-Bollatti et al: RUMEN-PROTECTED CHOLINE AND BODY CONDITION Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Choline has well-demonstrated lipotropic effects in laboratory animals (Cole et al, 2012) and dairy cows (Cooke et al, 2007;Elek et al, 2013;Zenobi et al, 2018b), and overconditioned prepartum dairy cows have an increased risk of fatty liver (Bobe et al, 2004). Therefore, it is reasonable to suggest that potential effects of choline on improving lipid intermediary metabolism and lactation performance might be more easily observed in cows at an increased risk for hepatic lipido-Bollatti et al: RUMEN-PROTECTED CHOLINE AND BODY CONDITION Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…lipids in part because of a small content of phosphatidylcholine in the intestine (da Silva et al, 2015), which impairs the secretion of chylomicron into lymph (Takahashi et al, 1982). In nonlactating dairy cows after feed restriction and subsequent fat challenge, RPC increased mean plasma concentration of triacylglycerol compared with nonsupplemented controls (Zenobi et al, 2018b), thereby suggesting that choline enhances the absorptive capacity of the gastrointestinal tract. Therefore, it is possible that nutrient absorption might be improved by choline, particularly lipids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results seem to be in contrast with several studies in which choline was shown to improve the metabolic health and liver function (5,12,13,26,30). In fact, Zenobi et al (44) stated that feeding pregnant, nonlactating Holstein cows with increasing amounts of RPC (from 0 to 25.8 g/d) decreased the concentration of hepatic triglycerides in a linear manner. Dietary choline thus seems to improve fat metabolism in the liver and increase the apparent absorption/traffic of triglycerides in the bloodstream, further confirming the beneficial effects of supplemental RPC for adult ruminants.…”
Section: Cholinementioning
confidence: 62%